(untitled) (Abhat Journal, 2025)
This study aimed to explore the relationship between the internal work environment and voluntary work turnover by studying the relationship`s dimensions of the internal work environment on voluntary work turnover. The study was conducted in four private school in the city of Misurata and used descriptive and analytical methods. The study`s population consisted of (343) teachers from a private school. , the study sample consisted of (184) individuals who were randomly selected. The study used a number of statistical methods for the analysis of data. The data was analysed using statistical methods. The study reached a number of results, the most important of which are: There is a direct relationship between the internal work environment and voluntary work turnover, and the internal work environment is appropriate in private school, where the general arithmetic average reached (3.90), also the voluntary work turnover variable was moderate and reached the general arithmetic mean (3.70), and the study recommended the necessity of paying attention to the internal environment with all its elements on ongoing basis and introducing improvement in the technology used in work environment, there is also a need to improve the material and moral incentive systems to achieving job stability in schools.